2018
DOI: 10.22460/jiml.v1i3.p248-255
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sq3r Strategy on Mathematical Communication Ability and Self Regulated Learning of Seventh Grade Student

Abstract: The study was a pre-test -post test experimental control group design having a goal to examine the role of SQ3R strategy and mathematics prior ability (MPA) on students’ mathematical communication ability  (MCA) and self regulated learning (SRL). The study involved 68 seventh grade students, a mathematical communication test, a mathematical  SRL scale, and a perception on SQ3R strategy scale. The study found that on MCA, its Gain, and on SRL students getting treatment by SQ3R strategy attained better grades th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Previously, researchers investigated various studies on students' mathematical communication, both at the secondary school level and at the college level, test students' mathematical communication skills through Treffinger's learning model, overall results, achievements and improve communication skills of students who get Treffinger's learning higher than students who get conventional learning [21]. Barnas examine the role of SQ3R strategies in students' mathematical communication skills and self-regulated learning, it was concluded that SQ3R class students had achieved better quality than the quality of students who received conventional learning [5]. Testing the mathematical communication skills of vocational students with guided inquiry models, the results show that mathematical communication skills of experimental class students are better than conventional class students [22].…”
mentioning
confidence: 99%
“…Previously, researchers investigated various studies on students' mathematical communication, both at the secondary school level and at the college level, test students' mathematical communication skills through Treffinger's learning model, overall results, achievements and improve communication skills of students who get Treffinger's learning higher than students who get conventional learning [21]. Barnas examine the role of SQ3R strategies in students' mathematical communication skills and self-regulated learning, it was concluded that SQ3R class students had achieved better quality than the quality of students who received conventional learning [5]. Testing the mathematical communication skills of vocational students with guided inquiry models, the results show that mathematical communication skills of experimental class students are better than conventional class students [22].…”
mentioning
confidence: 99%